2015
DOI: 10.1128/iai.03057-14
|View full text |Cite
|
Sign up to set email alerts
|

A Candida albicans Strain Expressing Mammalian Interleukin-17A Results in Early Control of Fungal Growth during Disseminated Infection

Abstract: dCandida albicans is normally a commensal fungus of the human mucosae and skin, but it causes life-threatening systemic infections in hospital settings in the face of predisposing conditions, such as indwelling catheters, abdominal surgery, or antibiotic use. Immunity to C. albicans involves various immune parameters, but the cytokine interleukin-17A (IL-17A) (also known as IL-17) has emerged as a centrally important mediator of immune defense against both mucosal and systemic candidiasis. Conversely, IL-17A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…IL‐17 induces the production of chemokines in the vagina in C. albicans infection, and chemokines may induce neutrophils recruitment. Huppler et al transformed an IL‐17‐expressing cassette into C. albicans and reported that IL‐17 expression did not adversely affect the growth of this species but reduced its pathogenicity in a systemic model of Candida infection 99 . It is noteworthy that susceptibility to Candida infections increases when IL‐17 is not produced, such as in patients with defects in genes involved in differentiation of Th17 cells, autoimmune polyglandular syndrome type 1 (APS1), Job's syndrome, and deficiency of Candida receptors (Dectin‐1 and CARD9) 100 .…”
Section: Immunological Aspects Of Vvc and Rvvcmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐17 induces the production of chemokines in the vagina in C. albicans infection, and chemokines may induce neutrophils recruitment. Huppler et al transformed an IL‐17‐expressing cassette into C. albicans and reported that IL‐17 expression did not adversely affect the growth of this species but reduced its pathogenicity in a systemic model of Candida infection 99 . It is noteworthy that susceptibility to Candida infections increases when IL‐17 is not produced, such as in patients with defects in genes involved in differentiation of Th17 cells, autoimmune polyglandular syndrome type 1 (APS1), Job's syndrome, and deficiency of Candida receptors (Dectin‐1 and CARD9) 100 .…”
Section: Immunological Aspects Of Vvc and Rvvcmentioning
confidence: 99%
“…Huppler et al transformed an IL-17-expressing cassette into C. albicans and reported that IL-17 expression did not adversely affect the growth of this species but reduced its pathogenicity in a systemic model of Candida infection. 99 It is noteworthy that susceptibility to Candida infections increases when IL-17 is not produced, such as in patients with defects in genes involved in differentiation of Th17 cells, autoimmune polyglandular syndrome type 1 (APS1), Job's syndrome, and deficiency of Candida receptors (Dectin-1 and CARD9). 100 Nevertheless, the loss of only one functional allele in Dectin-1 has no major effect on susceptibility to RVVC, and complete loss of function in this molecule is associated with a significant risk of infection 96 Dectin-1 abnormalities have not been found in women with idiopathic RVVC.…”
Section: Innate Immune Systemmentioning
confidence: 99%
“…Of particular interest is the central role of IL-17A in orchestration of antifungal defences. IL-17A and associated effector molecules and cells are potently induced in response to C. albicans infection, [38][39][40][41] with candidalysin accounting for robust induction of early and innate 'natural' Th17 cell-derived IL-17A. 20 Notably, elevated incidence or sensitization to C. albicans is often observed in a specific group of IL-17-mediated pathologies localized at mucosal and epithelial surfaces.…”
Section: Il-17-mediated Disordersmentioning
confidence: 99%
“…Of particular interest is the central role of IL‐17A in orchestration of antifungal defences. IL‐17A and associated effector molecules and cells are potently induced in response to C. albicans infection, 38–41 with candidalysin accounting for robust induction of early and innate ‘natural’ Th17 cell‐derived IL‐17A 20 …”
Section: Il‐17‐mediated Disordersmentioning
confidence: 99%